DEVELOPING CRITICAL THINKING THROUGH ENGLISH LANGUAGE LEARNING - Tatyana Trigulova; Madinabonu Fayzullayeva (Лучшие интеллектуальные исследования, 2024)
Annotation: Critical thinking skills are essential for personal and professional success in today's complex and interconnected world. These skills help individuals analyze information, evaluate arguments, and make reasonable decisions. Although the main goal of learning English is to improve communication skills, studying the language also presents a special chance to sharpen critical thinking abilities. This article explains the connection between English language learning and the cultivation of critical thinking and also introduces several pedagogical strategies for integrating these skills into the classroom.